2021
DOI: 10.1158/0008-5472.can-20-3773
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating B Lymphocyte Profiling Identifies IgG-Biased, Clonally Expanded Prognostic Phenotypes in Triple-Negative Breast Cancer

Abstract: In breast cancer, humoral immune responses may contribute to clinical outcomes, especially in more immunogenic subtypes. Here we investigated B lymphocyte subsets, immunoglobulin expression, and clonal features in breast tumors, focusing on aggressive triple-negative breast cancers (TNBC). In samples from TNBC patients and healthy volunteers, circulating and tumor-infiltrating B lymphocyte (TIL-B) were evaluated. CD20 + CD27 + IgDisotype-switched B lymphocytes were increased in tumors, compared with matched bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…11 TIB cells have been associated with chronic inflammatory signatures [15][16][17][18]37 and have been shown to secrete several inflammatory cytokines in breast cancer 38 . While previous studies have shown that tumor cells are capable of activating inflammatory signaling cascades in B cells 35,38 , the effects of this interaction on tumor cells are less clear. We therefore sought to determine the effects of B cells on tumor cells in co-culture studies with primary peripheral B cells isolated from the blood of TNBC patients.…”
Section: B Cells Induce Chronic Inflammation In Tnbcmentioning
confidence: 91%
See 1 more Smart Citation
“…11 TIB cells have been associated with chronic inflammatory signatures [15][16][17][18]37 and have been shown to secrete several inflammatory cytokines in breast cancer 38 . While previous studies have shown that tumor cells are capable of activating inflammatory signaling cascades in B cells 35,38 , the effects of this interaction on tumor cells are less clear. We therefore sought to determine the effects of B cells on tumor cells in co-culture studies with primary peripheral B cells isolated from the blood of TNBC patients.…”
Section: B Cells Induce Chronic Inflammation In Tnbcmentioning
confidence: 91%
“…The presence of IgG4 antibodies has been reported in a subset of cancer types, namely melanoma [28][29][30] , extrahepatic cholangiocarcinoma 31 , glioblastoma 32 , pancreatic cancer 33 , and hepatocellular carcinoma 34 and has been shown to have a negative correlation with recurrence free and overall survival 29,30,34 . Although the role of IgG4 in breast cancer is unclear, a recent study reported an enrichment of IgG+ clonally expanded B cells in TNBC, with an increase in IgG4 class switching in TNBC compared to non-TNBC 35 . In this study we sought to understand the mechanisms driving IgG4 class switching in TNBC and determine the relationship of IgG4+ B cells in the TME to patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Dealing with tumor antigens, that are closer to 'self' would then require more selective and high affinity antibodies. This possibility may be relevant in the context of disease, where the frequency of tumor infiltrating B cells in the tumor microenvironment or in the tertiary lymphoid structures (TLS) is related to a positive outcome against cancer aggressiveness (82)(83)(84)(85)(86). And then there is the cost of the system, which is much higher for the multi-stage process leading to the antibodies with highest affinity.…”
Section: Modeling the Gcbc Recycling Processmentioning
confidence: 99%
“…The heavy chain and light chain each have three complementarity-determining regions (CDRs), which largely determine the BCR's target specificity. (1,2) Characterising the BCR repertoire of an individual has proven to be a valuable tool for understanding the fundamental biology of B cells (3) as well as characterising changes during disease (4)(5)(6)(7). There are also clinical applications of BCR repertoire analysis in finding novel diagnostics, and therapeutic antibody discovery.…”
Section: Introductionmentioning
confidence: 99%